Analisis Pengaruh Kepemimpinan Transformasional, Budaya Organisasi Dan Loyalitas Kerja Terhadap Kinerja Karyawan Pada Pt. Hotel Citi Inn Medan - Sahat Simbolon; Beatrice Nathania (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2023)
This study aims to describe effect of transformational leadership, organizational culture, employee loyalty on employee performance at PT.Hotel Citi Inn Medan which lasted for 3 (three) months starting from February 2022 till April 2022.Simple random sampling used as sampling method on this research. All 64 employees of PT Hotel Citi Inn were respondents to this research. The Instrument used is questionnaire to collect data of transformational leadership variable, organizational culture variable, employee loyalty variable and employee variable. Data analysis technique on this research are valiity test, reliability test, descriptive analysis, multicolinearity test, normalty test, heterocedacity test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hyphotesis test or t test, silmutananeous test or F test, and calculation of coefficient determination.The result of descriptive analysis for all transformational leadership, organizational culture, employee loyalty and employee performance are in good category at PT Hotel Citi Inn Medan. Based on partial analysis conducted, transformational leadership, organizational culture, employee loyalty have a positive and significant effect on employee performance at PT Hotel Citi Inn Medan. Silmutaneously, transformational leadership, organizational culture, employee loyalty have positive and significant influence on employee performance at PT Hotel Citi Inn Medan. Contribution of transformational leadership, organizational culture and employee loyalty to improve empoyee performance are 0,833 or 83,3%., while the rest of 0.167 or 16,7% influenced by other variable not conducted on this research such as motivation, dicipline, communication, training, etc.